2008
DOI: 10.21608/ejabf.2008.2009
|View full text |Cite
|
Sign up to set email alerts
|

A protective effect of calcium carbonate against arsenic toxicity on the Nile catfish, larias gariepinus

Abstract: The present study was intended to test the protective upshot of calcium carbonate against the gifted toxicity of arsenic to the Nile cat-fish (Clarias gariepinus). Enhanced hepatosomatic index (HSI) and reduced gonadosomatic index (GSI) and intestinal index (ISI) as well as some of the tested blood parameters were recorded for fishes down to arsenic spotlight. The plasma levels of aspartate aminotransferase (AST, EC 2.6.1.1), alanine aminotransferase (ALT, EC 2.6.1.2), total bilirubin, direct bilirubin, total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…The range of arsenic concentrations inducing effects in the PHLC1 cell line and the zebra fish liver cells and JP and T0-2 are similar to those found to induce cellular level changes in whole organisms (Abdel-Hameid, 2009). After 9 days of exposure to sub-lethal concentrations of arsenic, the nile catfish showed biochemical and histological changes.…”
Section: Discussionsupporting
confidence: 66%
“…The range of arsenic concentrations inducing effects in the PHLC1 cell line and the zebra fish liver cells and JP and T0-2 are similar to those found to induce cellular level changes in whole organisms (Abdel-Hameid, 2009). After 9 days of exposure to sub-lethal concentrations of arsenic, the nile catfish showed biochemical and histological changes.…”
Section: Discussionsupporting
confidence: 66%
“…Similar trends were also evidenced in liver (39.85% and 25.26%) and gill (19.13% and 8.09%) tissue of the fish exposed to cyanide (Table 2). Increased activity of LDH is a characteristic feature of a shift from aerobic to anaerobic metabolism leading to elevated rate of pyruvate conversion into lactate, resulting in lactic acidosis (Abdel-Hameid, 2009). Data from the present study demonstrated a significant increase in LDH activity under hypoxia.…”
Section: Resultssupporting
confidence: 53%
“…This may probably be a result of loss of appetite due to the presence of antinutritional factors in banana peels and concomitantly resulted in reduction of total body weight (Abdel-Hamed, 2009). This result is also in agreement with several other works where changes in intestinosomatic index values were used as indicator of physiological conditions and body weight loss caused by reduced feed intake (Abdel-Tawwab et al, 2006.…”
Section: Resultsmentioning
confidence: 99%